1997
DOI: 10.1148/radiology.205.3.9393528
|View full text |Cite
|
Sign up to set email alerts
|

Small (1.5 cm or less) liver metastases: US-guided biopsy.

Abstract: US appears to be an effective guidance technique for biopsy of small liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Abdominal US-guided biopsy has adequate efficiency and low diagnostic and interventional costs. The diagnostic accuracy of US-guided interventions of the liver is 93-98% for lesions smaller than 1.5 cm and short access routes [17,18]. However, less than half of all focal liver lesions smaller than 1.5 cm (48%) are detected by US [19].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal US-guided biopsy has adequate efficiency and low diagnostic and interventional costs. The diagnostic accuracy of US-guided interventions of the liver is 93-98% for lesions smaller than 1.5 cm and short access routes [17,18]. However, less than half of all focal liver lesions smaller than 1.5 cm (48%) are detected by US [19].…”
Section: Discussionmentioning
confidence: 99%
“…Also of note, in cases in which biopsy is deemed the most appropriate clinical approach, some authors have reported that sonographic guidance provides an effective method. 23,24 Clearly, the next step in assessing the role of sonography in this clinical setting would be a well-designed prospective study optimally including comparison of the diagnostic efficacy and cost-effectiveness between the previously mentioned options.…”
mentioning
confidence: 99%
“…Turkay et al 8 found accuracy 73% to 94 %. Middleton et al 13 and Fisher et al 14 also found accuracy of ultrasonography, which were 93.0% and 86.0% respectively. The present study strongly supports the above mentioned studies.…”
Section: Discussionmentioning
confidence: 91%